Research Deserts: A Systematic Mapping Review of U.S. Rural Education Definitions and Geographies - Michael Thier; Jesse Moon Longhurst; Phillip D. Grant; Jessica Hocking (Journal of Research in Rural Education, 2021)
U.S. education research about rural places commonly neglects definitional boundaries. Our systematic mapping review 524 studies approximated how early-career scholars and those new to the rural education research space, including practitioners and policymakers, might experience the literature base and provides a bird's-eye view of how studies tend to define rurality and the types of locations, sectors, and participant roles that they interrogate within inquiries of rural education. We found definitions or demonstrations of rurality in 30% of our sample and little common ground among such studies. For example, 8.59% of studies in our sample applied the National Center for Education Statistics' urban-centric locale codes, still making that the most frequently employed schema. Defining rural occurred about twice as often within articles in rural-focused journals than within non-rural-focused journals, while articles in Journal of Research in Rural Education defined rural nearly three times as often as articles in non-rural-focused journals. Regionally, we found considerable evidence that site selection has tended to privilege the South and Midwest, seeming to desert the Northeast, Upper Midwest, and swaths of the West. Regarding sectors, we found rural research on K-12 education (81%) to be far more prevalent than on pre-K (1.15%) or tertiary education (12%). We conclude with provocations for U.S. education researchers toward a goal of richer scholarship.